DNA primase large subunit is an essential plant gene for geminiviruses, putatively priming viral ss-DNA replication - Siskos, Lampros; Antoniou, Maria; Riado, Jose; Enciso, Montserrat; Garcia, Carlos; Liberti, Daniele; Esselink, Danny; Baranovskiy, Andrey G.; Tahirov, Tahir H.; Visser, Richard G. F.; Kormelink, Richard; Bai, Yuling; et al. (Frontiers in Plant Science, 2023)
The family of Geminiviridae consists of more than 500 circular single-stranded (ss) DNA viral species that can infect numerous dicot and monocot plants. Geminiviruses replicate their genome in the nucleus of a plant cell, taking advantage of the host’s DNA replication machinery. For converting their DNA into double-stranded DNA, and subsequent replication, these viruses rely on host DNA polymerases. However, the priming of the very first step of this process, i.e. the conversion of incoming circular ssDNA into a dsDNA molecule, has remained elusive for almost 30 years. In this study, sequencing of melon (Cucumis melo) accession K18 carrying the Tomato leaf curl New Delhi virus (ToLCNDV) recessive resistance quantitative trait locus (QTL) in chromosome 11, and analyses of DNA sequence data from 100 melon genomes, showed a conservation of a shared mutation in the DNA Primase Large subunit (PRiL) of all accessions that exhibited resistance upon a challenge with ToLCNDV. Silencing of (native) Nicotiana benthamiana PriL and subsequent challenging with three different geminiviruses showed a severe reduction in titers of all three viruses, altogether emphasizing an important role of PRiL in geminiviral replication. A model is presented explaining the role of PriL during initiation of geminiviral DNA replication, i.e. as a regulatory subunit of primase that generates an RNA primer at the onset of DNA replication in analogy to DNA Primase-mediated initiation of DNA replication in all living organisms.